2004
DOI: 10.1590/s1678-77572004000300008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage solution on enamel demineralization submitted to pH cycling

Abstract: Extracted human teeth are frequently used for research or educational purposes. Therefore, it is necessary to store them in disinfectant solutions that do not alter dental structures. Thus, this study evaluated the influence of storage solution on enamel demineralization. For that purpose, sixty samples were divided into the following groups: enamel stored in formaldehyde (F1), stored in thymol (T1), stored in formaldehyde and submitted to pH cycling (F2), stored in thymol and submitted to pH cycling (T2). All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
1
10
0
6
Order By: Relevance
“…It has been reported that sodium hypochlorite may increase enamel porosity by deproteinization and alter dentin structure, by removing or modifying the proteic matrix, which could nullify the use of teeth stored in this solution. 19,20 Brauer et al studied effect of sterilization by gamma radiation on nano-mechanical properties of teeth and found no significant doseeresponse relationship in elastic modulus or hardness in either dentin or enamel. 6 Lee et al evaluated the effect of storage medium and sterilization on dentin bond strengths and found that storing teeth in 5.25% sodium hypochlorite may negatively affect composite-to-dentin bond strengths.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sodium hypochlorite may increase enamel porosity by deproteinization and alter dentin structure, by removing or modifying the proteic matrix, which could nullify the use of teeth stored in this solution. 19,20 Brauer et al studied effect of sterilization by gamma radiation on nano-mechanical properties of teeth and found no significant doseeresponse relationship in elastic modulus or hardness in either dentin or enamel. 6 Lee et al evaluated the effect of storage medium and sterilization on dentin bond strengths and found that storing teeth in 5.25% sodium hypochlorite may negatively affect composite-to-dentin bond strengths.…”
Section: Discussionmentioning
confidence: 99%
“…[6] It has been reported that sodium hypochlorite may increase enamel porosity by deproteinization and alter dentin structure by removing or modifying the protein matrix, which could nullify the use of teeth stored in this solution. [2021] Hence, an appropriate disinfectant that overcomes these limitations is required, as extracted human teeth are commonly used in dental institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence in this study, 0.01% thymol solution was used as a storage solution and disinfectant. [3] Some studies show that pumice prophylaxis does not completely and consistently remove the pellicle and debris, especially in the depth of the fissure. [18] Studies by Blackwood JA et al .…”
Section: Discussionmentioning
confidence: 99%
“…The teeth were then dried with a mild oil-free air stream to achieve a characteristic frosty white, chalky appearance of enamel. [3] Two coats of bonding agent (G bond, GC) were applied (using applicator on the etched tooth surface) and light cured for 20 seconds using visible light curing unit (470 nm to 420 nm wavelength). Sealants were then applied and cured according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%